Bangladesh and SAARC Countries: Bilateral Trade and Flaring of Economic Cooperation - Md. Abu Issa Gazi; Abdullah Al Masud; Razuan Ahmed Shuvro; Abu Ishaque Hossain; Muhammad Khalilur Rahman (Faculty of Economic and Business, 2022)
The primary purpose of this study is to observe the economic andinternational trade relationships between Bangladesh and SAARCcountries during the Fiscal Years 2015-2016 to 2020-2021. Thisresearch uses panel data to examine the relationship betweenthe nature and direction of exports and economic growth.The researcher found that economic cooperation with SAARCcountries impacted economic growth, but there was insufficientexport adaptation. The study also showed that economic relationshave strengthened in recent epochs, and bilateral trade hasincreased compared to previous years with SAARC countries.The obtained results also showed that Bangladesh has sufferedfrom a long-standing trade imbalance with India and is in agood position with Afghanistan, Sri Lanka, Bhutan, Maldives,Nepal, and Pakistan. Our findings are beneficial for internationaltrade stakeholders and suggest that steps should be taken toincrease exports to reduce the trade deficit. Concern authoritiesshould be more aware of the expansion of trade facilitation andinfrastructure development.JEL Classification: F5, F18, F23, F50, M16